Adolescent Choline Supplementation Attenuates Working Memory Deficits in Rats Exposed to Alcohol During the Third Trimester Equivalent - Schneider, Ronald D. (Alcohol Clin Exp Res, 2016)
BACKGROUND: Children exposed to alcohol prenatally may suffer from behavioral and cognitive alterations that adversely affect their quality of life. Animal studies have shown that perinatal supplementation with the nutrient choline can attenuate ethanol’s adverse effects on development; however, it is not clear how late in development choline can be administered and still effectively reduce the consequences of prenatal alcohol exposure. Using a rodent model, this study examined whether choline supplementation is effective in mitigating alcohol’s teratogenic effects when administered during adolescence/young adulthood. METHODS: Sprague–Dawley rats were exposed to alcohol (5.25 g/kg/d) during the third trimester equivalent brain growth spurt, which occurs from postnatal day (PD) 4 to 9, via oral intubation. Sham-intubated and nontreated controls were included. Subjects were treated with 100 mg/kg/d choline chloride or vehicle from PD 40 to 60, a period equivalent to young adulthood in the rat. After the choline treatment had ceased, subjects were tested on a series of behavioral tasks: open field activity (PD 61 to 64), Morris water maze spatial learning (PD 65 to 73), and spatial working memory (PD 87 to 91). RESULTS: Ethanol-exposed subjects were overactive in the activity chambers and impaired on both the spatial and the working memory versions of the Morris water maze. Choline treatment failed to attenuate alcohol-related overactivity in the open field and deficits in Morris water maze performance. In contrast, choline supplementation significantly mitigated alcohol-related deficits in working memory, which may suggest that choline administration at this later developmental time affects functioning of the prefrontal cortex. CONCLUSIONS: The results indicate that adolescent choline supplementation can attenuate some, but not all, of the behavioral deficits associated with early developmental alcohol exposure. The results of this study indicate that dietary intervention may reduce some fetal alcohol effects, even when administered later in life, findings with important implications for adolescents and young adults with fetal alcohol spectrum disorders.